Antibiotic, heavy metal, and disinfectant resistance in chicken, cattle, and sheep origin E. coli and whole‐genome sequencing analysis of a multidrug‐resistant E. coli O100:H25 strain. Issue 5 (31st May 2022) - Cufaoglu, Gizem; Cengiz, Gorkem; Onaran Acar, Bahar; Yesilkaya, Busra; Ayaz, Naim Deniz; Levent, Gizem; Goncuoglu, Muammer
Abstract: In this study, antibiotic, heavy metal, and disinfectant resistance profiles of E. coli and E. coli O157 isolates were determined, and whole‐genome sequencing of a multidrug‐resistant E. coli O100:H25 strain was reported. A total of 70 E. coli isolated from chicken neck skin and sheep cecum samples, and 32 E. coli O157 strains isolated from cattle carcass, sheep carcass, and slaughterhouse wastewater samples were explored. Minimum inhibitory concentrations (MICs) of one antibiotics, eight heavy metals, and three disinfectants were determined by the broth microdilution method. Twenty of those isolates exhibiting high MIC values against compounds tested were further analyzed by PCR for the presence of relevant resistance genes ( n = 42). The majority of the isolates tested were resistant to erythromycin and/or fosfomycin (99% and 78%, respectively) and 89% of the isolates were multidrug‐resistant. Among the heavy metals, and disinfectants that were quaternary ammonium compounds (QAC) tested, the highest prevalence of resistance was observed against nickel (71%) and followed by zinc (62%), and N‐alkyl‐dimethyl‐benzyl‐ammonium chloride (26%). While bla AmpC, ermC, murA, and aadA were the most abundant antibiotic resistance genes, rcnA and zntA, and mdfA, sugE (c), and ydg(F) were also commonly observed as heavy metal and disinfectant genes, respectively. Additionally, whole‐genome sequencing was performed for a single multidrug‐resistant strain ( E. coli P91). This strain was identified as serotype O100:H25, and harbored three Inc class plasmids and ant(2″)‐Ia, aph(3′)‐Ia, aph(3″)‐Ib, aph(6)‐Id, bla TEM‐1A, dfrA5, mdf(A), sul1, sul2, and tet (A) genes along with the various heavy metal and disinfectant related genes. The findings of the study show that both phenotypic and genotypic antibiotic, heavy metal, and disinfectant resistance are highly prevalent in E. coli isolates that originated from food‐producing animals . The use of antimicrobials in food‐producing animals needs to be carefully evaluated since the coexistence of antibiotic, heavy metal, and disinfectant resistance genes may result in a coselection that yields the emergence and spread of highly persistent and resistant strains in agricultural settings. Abstract : This research highlights the emergence of antibiotic, heavy metal, and disinfectant resistance in E. coli in food‐producing animals, and sheds light on a multidrug‐resistant E. coli O100:H25 strain by WGS.